The Emerging Role of Neural Cell-Derived Exosomes in Intercellular Communication in Health and Neurodegenerative Diseases - Huo, Luyao; Du, Xinzhe; Li, Xinrong; Liu, Sha; Xu, Yong (Frontiers in Neuroscience, 2021)
Intercellular communication in the central nervous system (CNS) is essential for brain growth, development, and homeostasis maintenance and, when dysfunctional, is involved in the occurrence and development of neurodegenerative diseases. Increasing evidence indicates that extracellular vesicles, especially exosomes, are critical mediators of intercellular signal transduction. Under physiological and pathological conditions, neural cells secret exosomes with the influence of many factors. These exosomes can carry specific proteins, lipids, nucleic acids, and other bioactive substances to the recipient cells to regulate their function. Depending on the CNS environment, as well as the origin and physiological or pathological status of parental cells, exosomes can mediate a variety of different effects, including synaptic plasticity, nutritional metabolic support, nerve regeneration, inflammatory response, anti-stress effect, cellular waste disposal, and the propagation of toxic components, playing an important role in health and neurodegenerative diseases. This review will discuss the possible roles of exosomes in CNS intercellular communication in both physiologic and neurodegenerative conditions.